Normal sperm parameters per se do not reliably account for fertility: A case–control study in the real‐life setting. (30th October 2020) - Boeri, Luca; Belladelli, Federico; Capogrosso, Paolo; Cazzaniga, Walter; Candela, Luigi; Pozzi, Edoardo; Valsecchi, Luca; Papaleo, Enrico; Viganò, Paola; Abbate, Costantino; Pederzoli, Filippo; Alfano, Massimo; et al.
Abstract: A proportion of men are infertile despite having normal medical history/physical examination and normal semen analysis. We aimed to assess whether normal sperm parameters per se account for male factor fertility. 1, 957 infertile men were compared with 103 age‐comparable fertile controls. Semen analysis was based on 2010 World Health Organization reference criteria. Of all, 12.1% of infertile men and 40.8% of fertile men presented with normal sperm parameters. Among fertile men, 36.9% had isolated sperm abnormalities and 22.3% men showed two or more concomitant sperm abnormalities. Serum total testosterone was higher in infertile men with normal sperm parameters compared to those with ≥2 sperm abnormalities or azoospermia, but similar to those with isolated sperm abnormalities ( p ≤ .001). Circulating hormones were similar among sperm parameters groups in fertile men. At multivariable analyses, testicular volume (OR 1.12, p ≤ .001) and FSH (OR 0.8, p ≤ .001) were associated with normal sperm parameters. Overall, the longer the infertility period, the greater the number of sperm parameters abnormalities ( p < .01). In conclusion, we found that 12% of infertile men and only 41% of fertile men present with normal sperm parameters. Normal sperm parameters per se do not reliably account for fertility in the real‐life setting.